Strategic planning for human resources and its impact on Sudanese national security - Abu Zeid, Mu'tasim Hussein (Journal of Economic, Administrative and Legal Sciences, 2019)
The study considered the importance of strategic planning for human resources and its impact on Sudanese national security considering that strategic planning is one of the important mechanisms that achieve integration and interaction between the components of the comprehensive perspective of human resources at the state level, in order to achieve the conditions required to achieve the full utilization of competitive human capabilities as one of the important elements affecting national security. The study aimed at the importance of strategic planning for human resources at the macro level of the state and its impact on Sudanese national security. The study reviewed the terms related to strategic planning, the concept of national security and the relationship between strategy, national security and human resources. The study reviewed the terms related to strategic planning, the concept of national security and the relationship between strategy, national security and human resources. The study also dealt with the aspects affecting the human resources and the Sudanese reality. The descriptive approach was used for the study and the scientific sources that dealt with the subject were used as sources for the study. The study concluded that strategic planning for human resources should be adopted, and that a national policy should be established through human resource development programs and clear foundations for investing human resources to meet challenges related to human capabilities, especially competitive human capacities.